2012
DOI: 10.2217/whe.12.11
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Postmenopausal Testosterone Therapy

Abstract: Testosterone is increasingly used as part of postmenopausal HRT regimens. Unfortunately, few androgenic preparations designed specifically for use in women have been approved by regulatory authorities. Ongoing concerns exist surrounding the potential long-term effects of testosterone therapy. Here, we review the most recent data on postmenopausal testosterone therapy, focusing particularly on the effects of testosterone on breast, endometrium and cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Oral testosterone therapy increases triglycerides and low-density lipoprotein cholesterol and reduces high-density lipoprotein cholesterol. These adverse lipid effects have raised concern regarding safety [52]. In 967 surgically menopausal women who were also on estrogen replacement, transdermal testosterone therapy did not affect lipid profiles over 4 years of follow up [53].…”
Section: Treatmentsmentioning
confidence: 99%
“…Oral testosterone therapy increases triglycerides and low-density lipoprotein cholesterol and reduces high-density lipoprotein cholesterol. These adverse lipid effects have raised concern regarding safety [52]. In 967 surgically menopausal women who were also on estrogen replacement, transdermal testosterone therapy did not affect lipid profiles over 4 years of follow up [53].…”
Section: Treatmentsmentioning
confidence: 99%
“…Giving testosterone via the transdermal route avoids first-pass metabolism in the liver and leads to more physiological and stable serum levels. 17 A systematic review and large meta-analysis of the safety of the transdermal patch showed that no changes in serum lipid profile, renal, liver function or blood cell indices were seen with transdermal testosterone. 18 Testosterone does not appear to stimulate the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Transdermal testosterone does not appear to stimulate the endometrium [101][102][103] ; nor does it appear to increase mammographic breast density 95,104,105 or elevate breast cancer risk. 78,96,98 Because testosterone aromatizes to estradiol, there have been some concerns that it could have secondary stimulatory effects on the estrogen receptor.…”
Section: Breast and Endometriummentioning
confidence: 99%